Method of preparation and evaluation of Green synthesis silver nanoparticle: An updated review - RAVINDRA B CHINTAMANI,; KISHOR S SALUNKHE,; MACHINDRA J CHAVAN, (International Journal of Pharma and Bio Sciences, 2018)
This review gives prominence to green synthesis of silver nanoparticles (Ag-NP’s) using various plant extracts or phyto-constituents or microbial species and its applications and treatments in different chronic diseases. The development of eco-friendly and reliable techniques for green synthesis of silver nanoparticles is a vital step in the area of nanotechnology. The researchers pay more attention on silver nanoparticles (Ag-NP’s) because of their unique properties and applications in various fields such as medicine, catalysis, water treatment, nanoelectronics, pollution and textile field. The silver nanoparticles are synthesized by various chemical and physical methods. A variety of preparation techniques have been reported for the synthesis of silver NPs; notable examples include, laser ablation, gamma irradiation, electron irradiation, chemical reduction, photochemical methods, microwave processing etc. The major drawbacks of chemical and physical methods are the synthesis processes which are expensive as many toxic chemicals are used. To overcome these problems, green nanotechnology comes to play a precise key role for synthesis of silver nanoparticles and also to reflect the potentials and limitations of the above mentioned techniques for industries. Nanoparticles are referred as Green Nanotechnolgy because of using of various plants for the synthesis of silver NPs.Use of various plants for synthesis of biogenic silver nanoparticles referred as Green Nanotechnology.